Impediments to Unity in The Politics of Guyana: An Application of Partial Allocative Theories of Inputs - Green, Edward John (My University, 1966)
The study deals with the adaptations of the concept of Political System to the analysis of the Politics of Guyana. In forwarding his research, the author has focused attention on the element of "Stress" upon the Political System of Guyanese society. Sections an theory and comparative method have been organized in order to develop a framework of partial allocative theories of inputs. This instrument has been applied by assessing in turn, the environmental content of Guyanese society, patterns of demand and support behaviour, and in the formulation of proposals for an explanatory model of the process of national Political Development.
Keywords: Political Science; Political Science